Pengaruh Pendekatan Realistic Mathematics Education (RME) Terhadap Kemampuan Pemahaman Matematis Ditinjau Dari Kemampuan Awal Matematis Siswa - Ilma Nurfadilah; Hepsi Nindiasari; Abdul Fatah (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2020)
This research is motivated by the low ability of junior high school students' mathematical understanding and there are still students who are passive in the learning process. The learning approach can direct students to be active in the learning process, the approach taken is the Realistic Mathematics Education (RME) approach. Based on previous relevant research, it was stated that with the realistic mathematics education (PMR) approach, the increase in learning was higher than students who received regular learning at all students and all school levels. The research population was all students of SMP Mathla'ul Anwar Global School 2019/2020 academic year and the research sample was class VII with the design of The Randomized Pretest-Posttest Control Group Design, making two groups randomly, namely the experimental group and the control group by giving two different treatments. different. This study aims to determine: 1. Knowing the mathematical understanding ability of students who use the RME approach is better than students who use the scientific approach. 2. Determine whether there is an interaction between the learning approach and the initial mathematical ability (high, medium, low) on students' mathematical understanding abilities. The results showed: 1. The mathematical understanding ability of students who used the RME approach was better than students who used the scientific approach. 2. There is no interaction between the learning approach and early mathematical abilities (high, medium, low) on students' mathematical understanding abilities.